Pelatihan Proses Pembuatan Film Pendek sebagai Media Dakwah Siswa-Siswi SMA Nurul Ikhlas Kabupaten Tanah Datar - Annisa, Ana Citra; Yahya, Anandita; Indayani, Fajar; Syofany, Ginna (Lembaga Yasin AlSys, 2026)
The development of digital technology has encouraged the use of audiovisual media as an innovative learning tool, one of which is through short films that are able to convey messages effectively and engagingly. However, students’ ability to produce short films remains limited, both in technical and conceptual aspects, so structured training is needed. This study aimed to describe the form of training used to improve the understanding, skills, and creativity of students at SMA Nurul Ikhlas, Tanah Datar Regency, in the process of making short films while also utilizing them as a medium for da’wah. This study used a participatory descriptive approach through the stages of surveying and training implementation. The survey stage was conducted to identify students’ interests and needs, while the implementation stage included lecture, question-and-answer, and practicum methods. The training materials covered determining story ideas, scriptwriting, the production process, and editing. The results of the activity showed a significant increase in students’ understanding of storytelling concepts, technical skills in film production, and creativity. In addition, this activity had a positive impact on the development of soft skills, such as teamwork, communication, and critical thinking. Students’ enthusiasm and motivation also increased, as reflected in their active involvement throughout the training process. Thus, short film production training can serve as an effective alternative to project-based learning, is relevant to educational needs in the digital era, and has the potential to function as a creative and educational da’wah medium for the younger generation.